Institutional trap of degradation of the assortment of the computer equipment in the retail market of the Russian Federation - Borodin A. V., Ivanov D. I. (Scientific studies and modern education, 2018)
The phenomenon of origin of more than 15-year trend of lowering of the assortment of the computer equipment and accessories in the retail market in the Russian Federation is probed. The directions of the institutional transformations capable to break a negative trend are offered and to exert the positive impact on scientific and technical progress in the country.
Keywords: ассортимент; научно-технический прогресс; оборотный капитал; liberalization; либерализация; институциональная ловушка; налоговое законодательство; assortment; онтологический анализ; IDEF5; IDEF5; ontological analysis; налоговые каникулы; institutional trap; положительная обратная связь; positive feedback; трансформация институтов; tax code; tax exemption; scientific progress; working capital; transformation of institutes